Linking Sleep Patterns to Health Outcomes- A Systematic Review - K. Bhanu Teja; Kasireddy Swapna; Dev Prateek Patel; R. Yaswanth Kumar Reddy; Syed Hameed uddin; Chelmilla Pooja; Suthakaran Raj (International Journal of Pharmacy and Analytical Research, 2026)
Sleep is a fundamental physiological process that plays a critical role in maintaining overall health and well-being. Emerging evidence suggests that both sleep duration and sleep quality significantly influence metabolic regulation, psychological wellness, and endocrine balance. Disturbances in sleep are associated with alterations in hormonal regulation, particularly insulin and other appetite-regulating hormones, which can disrupt energy homeostasis, impair glucose metabolism, and contribute to body weight gain. Inadequate or poor-quality sleep has also been linked to increased risk of metabolic dysregulation, emphasizing its role in body weight regulation. Beyond metabolic effects, sleep is essential for the proper functioning of the endocrine system involved in reproductive health. Disruptions in sleep patterns and circadian rhythms can adversely affect the hypothalamic–pituitary–gonadal axis, leading to hormonal imbalances that may manifest as irregular menstrual cycles, altered menstrual duration, or changes in menstrual flow. These effects may be further intensified by chronic psychological stress, which elevates cortisol levels and interferes with reproductive and metabolic hormone balance. The relationship between sleep and stress is bidirectional, wherein psychological distress negatively affects sleep quality, while inadequate sleep heightens stress sensitivity and emotional dysregulation. Lifestyle factors play a crucial role in shaping sleep behaviors. Unhealthy lifestyle practices, including poor dietary habits, physical inactivity, irregular daily routines, and sedentary behavior, are commonly associated with sleep disturbances and hormonal imbalance. Conversely, healthy lifestyle practices promote adequate sleep and hormonal stability. Overall, sleep emerges as a modifiable determinant influencing metabolism, reproductive health, stress, and lifestyle-related health outcomes. Targeted lifestyle interventions and stress management strategies aimed at improving sleep may serve as effective approaches to enhance metabolic health, reproductive function, and quality of life.